ANALISIS PERHITUNGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 MENGGUNAKAN TARIF EFEKTIF RATA-RATA (TER) DI PT PELINDO MULTI TERMINAL - Khairul Anwar Pulungan; Indah Putri Aisyah (CERED Indonesia Institute, 2026)
Taxes are the main source of state revenue and play an essential role in supporting national development, making taxpayer compliance a crucial aspect. One of the types of taxes that contributes significantly is Income Tax Article 21, which is imposed on employee income. This study aims to analyze the calculation, payment, and reporting of Income Tax Article 21 using the Average Effective Rate (TER) at PT Pelindo Multi Terminal. The TER policy is regulated under Government Regulation No. 58 of 2023 and Minister of Finance Regulation No. 168 of 2023 as part of Indonesia’s tax reform, which is intended to simplify the administration of tax withholding while also enhancing taxpayer compliance. This research employs a descriptive qualitative method with data obtained through interviews, observation, and documentation. The results indicate that the implementation of TER has provided convenience in tax calculation and supported administrative efficiency. Nevertheless, several challenges remain regarding the timeliness of tax payments and reporting in certain periods, which may serve as an evaluation point for future improvements. Overall, the application of TER at PT Pelindo Multi Terminal has been in accordance with existing regulations and has contributed positively to supporting the company’s tax compliance.